The securitisation of life: Eastern Kurdistan under the rule of a Perso-Shi'i state. Issue 4 (2nd April 2020) - Soleimani, Kamal; Mohammadpour, Ahmad
Abstract: Since the 1979 Revolution, the Iranian state has adopted a sophisticated set of policies to assimilate the Eastern Kurds. The Kurds are often the main target of the Iranian state's military operations, its assimilatory strategies, and its regime of surveillance. After the 'conquest' ( fath ) of Eastern Kurdistan ( Rojhelat ) in 1979, the state tried to retain control over the region through systemic militarisation, the establishment of 'revolutionary institutions', and new religious and cultural centres, to transform the demographic, religious and cultural profile of Kurdistan. This paper is an attempt to illuminate the state's religious nationalism and various forms of assimilatory strategies that the Islamic Republic of Iran has employed to transform Kurdish regions.